2011
DOI: 10.1007/s12603-011-0072-y
|View full text |Cite
|
Sign up to set email alerts
|

Body circumferences are predictors of weight adjusted resting energy expenditure in older people

Abstract: These findings demonstrate that trunk circumferences, but not WHR, are very strong predictors of weight adjusted REE in non-geriatric older people. This implies that the sex-specific use of abdomen or hip circumference in combination with LBM or body height and BMI seems to be well sufficient to predict weight adjusted REE in the aged. These measures might also be of clinical relevance, because they are more comfortable for older sick people than indirect calorimetry. Further studies are needed to test the app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…It has been reported that including body composition data and some body circumference measurements, such as WC, improved the estimation of predictive equations [ 23 ]. This is particularly relevant for patients with obesity and older adults [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that including body composition data and some body circumference measurements, such as WC, improved the estimation of predictive equations [ 23 ]. This is particularly relevant for patients with obesity and older adults [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%